Environmental Pollution Assessment of Heavy Metals in Soils and Crops in Xinping Area of Yunnan Province, China - Shengchao Xu; Zhao Huang; Jiaxin Huang; Song Wu; Yan Dao; Zheng Chen; Baichun Yang; Yongqiang Xu; Ningqiang Liu; Qingjie Gong (Applied Sciences, 2023)
With the development of the economy and society, the environmental problems caused by heavy metals have always been the focus of attention. Strong concern has been recently shown for the heavy metal pollution of soils in southwestern China. The heavy metals of surface soils in the Xinping area of Yunnan province, China are surveyed along with some crop samples. There are 3312 surface soils and 95 crop samples collected in about 370 square kilometers. Heavy metals including As, Cd, Cr, Hg, and Pb and pH are analyzed. New single and integrated pollution indices of heavy metals for soils (PI and PIn) and crops (PIc and PInc) based on Chinese criteria (GB15618-2018 and GB2762-2022) are described and presented here and used to assess the pollution status of heavy metals. The results indicate that the background level of surface soils is about 62.1%, the screening level is about 33.4%, and the intervention level is about 4.5%, which is mainly a result from Cr and spatially coincides with the peridotite rock, indicating a geogenic pollution source. Most crop samples are not contaminated with heavy metals. Comparing the results of the two integrated pollution indices between soils and crops, two inconsistent assessments are observed. One is that some contaminated crops are growing in unpolluted areas (or Type I) and the other is that some uncontaminated crops are growing in polluted areas (or Type II). This indicates a new challenge between the assessment criteria on soils and crops.